Evolution of Image Receptors in Dental Radiology - Satya Sudarsini, Pernidi; N, Rajesh; R, Sudhakara Reddy (International Journal of Dental Materials, 2020)
The quality of a radiograph depicted by geometric and visual characteristics, in turn also depends on the quality of image receptors. Image receptors in dentistry have seen an enormous evolution trend from conventional x-ray films to the current generation of digital image receptors. The development of cost-effective image receptors is established in various types of imaging procedures. The current article provides an insight into the image receptors used in dental radiology.